2013
DOI: 10.1016/j.ejsobi.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasons and land-use practices on soil microbial activity and metabolic diversity in the “Montado ecosystem”

Abstract: a b s t r a c tThe "Montado ecosystem" is important both economically and ecologically; this ecosystem is dominated by cork and holm oak trees (Quercus suber L. and Quercus rotundifolia Lam. respectively) combined with a rotation of crops/fallow/pastures. Diverse management strategies, deviating from the sustainable use of the ecosystem, have been implemented, from which arise some extreme situations of over-use or abandonment. To evaluate the effects of different soil use and management, namely extensive crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…It seems that seasons drive the pattern of metabolic profile via influencing the moisture content of the soil. Our finding corroborates with reports of Costa et al [18] which indicated highest microbial activity in rainy season in cork and holm oak trees dominated Montado ecosystem. Li et al [19] have also showed higher microbial activity in rainy season and reasoned that the induced microbial growth due to increased soil moisture and temperature were the causal factors.…”
Section: Metabolic Diversity and Profilesupporting
confidence: 93%
“…It seems that seasons drive the pattern of metabolic profile via influencing the moisture content of the soil. Our finding corroborates with reports of Costa et al [18] which indicated highest microbial activity in rainy season in cork and holm oak trees dominated Montado ecosystem. Li et al [19] have also showed higher microbial activity in rainy season and reasoned that the induced microbial growth due to increased soil moisture and temperature were the causal factors.…”
Section: Metabolic Diversity and Profilesupporting
confidence: 93%
“…Various studies have used CLPPs to differentiate microbial communities in diverse land uses (Bossio et al ; Sun et al 2011 a ; Costa et al ). AWCD reflects the ability of a soil microbial community to use individual C sources and is an important indicator of microbial activity (Zabinski & Gannon ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, land use changes can reduce soil C and N sequestration, resulting in the acceleration of greenhouse gas (CO 2 and N 2 O) emissions 7 8 9 . Land-use changes also contribute to changes in microbial activities and biological processes that affect soil quality 10 11 .…”
mentioning
confidence: 99%